Molecular identification and genetic studies in Peruvian Phragmipediums - Rolando, Isaias; Rodríguez, M.; Damian, M.; Benavides, J.; Manrique, A.; Espinoza, J. (Lankesteriana: International Journal on Orchidology, 2015)
Peru has inherited one of the greatest biodiversities of the planet. The orchid genus Phragmipedium has several representatives in the country. They are listed in Appendix 1 of CITES, restricted from international trade.